Effect of geographical location, processing and simulated digestion on antioxidant characteristics of quince (Cydonia oblonga) - Baroni, María Verónica (2022)
Quince fruit (Cydonia oblonga Miller) is an important source of bioactive compounds, especially of phenolic compounds, that's why it is considered a good source of antioxidants. However, it is known that the antioxidant characteristics and the beneficial effect of foods are affected by the variety, geographical origin, processing and gastrointestinal digestion. In this work, the effects of the geographical origin, processing, and simulated digestion of quince jam on its antioxidant characteristics were studied. Phenolic composition and antioxidant capacity were determined in quince fruit and jam from four different locations in San Juan, Argentina. The results showed that quince fruit samples from St. Lucia had the highest total phenolic content (5.13 mg GAE/g; p < 0.05) and in vitro antioxidant capacity measured by ferric-reducing antioxidant power assay (FRAP) and radical-scavenging capacity assay (DPPH· and ABTS·+). With regard to quince jam, a positive effect was observed on its antioxidant characteristics after processing. Twenty-one phenolics were detected in jam, being most of them derivatives of hydroxycinnamic acids (eg. 5-caffeoylquinic acid; 4-caffeoylquinic acid and quinic acid). Studies on stability and bioaccessibility of quince phenolics showed that less than 25% of the initial phenolics in jam were detected after digestion being quinic acid and hydroxycinnamic acids the most resistant. The in vitro antioxidant capacity showed, in general, a similar trend to the phenolics content throughout the digestion process. The results obtained showed that the antioxidant activity of quince and jam is related to the type and amount of phenolics in the samples, which depends on the geographical origin, processing, and gastrointestinal digestion. These variables are not always taken into account when studying the probable antioxidant activity of food, even though they should be considered for a complete nutritional evaluation of a food.